To Assess the Awareness Amongst Parents Regarding the Effects of Exposure to Multimedia Screen-Time During Meals on Oral Cavity in Children Aged 7 to 12 Years- A Cross-Sectional Questionnaire- Based Study - Dr. Antik Bhattacharyya,; Dr. Sinjana Jana,; Dr. Snehasish Basu,; Dr. Shreya Tripathi,; Dr. Rajeswary De,; Dr. Rajat Dutta,; Moumita Basu, (The Bioscan, 2025)
Background: The aim of this study is to evaluate the level of knowledge and awareness among parents regarding the food pouching habit in children aged 7 to 12 years while using multimedia devices. Material and Method: A pre-validated Questionnaire was provided to the Parents for filling their responses. The questionnaire included Demographic details, knowledge-related and attitude-based questions related to the study. The total number of samples taken for the study was 300. Results: Out of 300 participants, 12 of them were unable to fill up responses accurately. Among the rest, around 63% of children watch various types of screen while eating meals. 78% of them hold food in their mouth without swallowing. Conversely, it has also been reported that around 13% of children do not use screens during meal time and still happen to hold the food in their mouth during meal. Conclusion: The study found that the parents have average understanding and awareness of the food-pouching habit of children that is related to increased risk of dental problems. It is also seen that children with both parents working have more tendency to often develop the habit of watching screens during mealtime, which encourages food pouching behavior. Thus more parental awareness regarding the same is necessary.